Can salt-adapted microorganisms alleviate salt stress in plants and enhance their non-specific resilience? - Margarita, Saubenova; Sviatoslav, Maksimovich; Yelena, Oleinikova; Makhpal, Yelubaeva (Frontiers in Agronomy, 2023)
Global climate change presents various challenges to agricultural biotechnology in developing crops with increased resilience to various adverse natural conditions. Given the importance of this problem, we explored the mechanisms of plant salt tolerance and the role of plant-associated microbes, in mediating important physiological and metabolic processes that increase plant resistance to salt stress. Understanding the physiological, metabolic, and molecular responses of the entire plant holobiont, primarily including microorganisms, to the combination of abiotic stresses may be the key to developing more effective methods of combating various stress conditions and increasing agricultural efficiency. This work encompassed 86 peer-reviewed articles focused on various aspects of plant development in saline conditions and especially on key mechanisms of mitigating stress conditions, including the role of rhizobiome and endophytic microorganisms. It is shown that host plants and various microorganisms can form complex relationships where each organism plays a specific role in forming tolerance to stress conditions. Our review proposes that studying microorganisms that are resistant to soil salinity can lead to the development of new strategies to combat salinization and improve crop stress resistance. The paper concludes that using salt-adapted biostimulant microorganisms, which are natural components of agricultural plant microbiomes, is a highly promising research area.